Lining of Open Channel with Jute Geotextile and its Performance in Seepage Control - Choudhury, M Roy; Chatterjee, P; Dey, P; Nag, D; Debnath, S; Ghosh, S K; Ganguly, P K (Journal of Agricultural Engineering, 2008)
Various lining materials such as precast channel, brick masonary, bituminous mixture, soil cement, polythene sheets etc. have so far been used for controlling seepage in irrigation channels. Some are too costly to be locally used while others have short life and are not much effective. Keeping it in view, this work was taken up to find out a viable alternative to these traditional materials. Jute non-woven geo-textile of 250 g/m² and 300 g/m² fabric weight were coated with polyethylene sheet on one side and both sides and were experimented to assess the seepage loss through open channels. 300 g/m² fabric with both sides coated controlled seepage most efficiently. Single side coated sheets also performed well in seepage control, but allowed more water to seep compared to double side coated sheets. However, 250 g/m² fabric with both sides laminated yielded optimum performance.